Performance Evaluation of SAMSAT Office Employees in Motor Vehicle Title Transfer Fee Services at The Rantauprapat SAMSAT Office - Ribkha Esterlita Pakpahan; Elida Florentina Sinaga Simanjorang; Yudi Prayoga (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This research aims to determine the performance of employees at SAMSAT in the Motor Vehicle Transfer of Title Fee Service at the SAMSAT Rantauprapat Office and to find out the relationship and contribution of each factor that influences the Performance of Employees in the Motor Vehicle Transfer of Title Fee Service at the SAMSAT Rantauprapat Office. The method in this research is a quantitative method. In this research, the population used is people who process motor vehicle transfer fees at the Rantauprapat SAMSAT office. The data analysis method used was multiple linear regression analysis, and hypothesis testing (partial test, simultaneous test, and coefficient of determination). Based on the results of the t-test, it is known that four of the five service quality indicators have a positive and significant effect on the quality of BBN-KB performance at the Rantauprapat SAMSAT Office. The service quality indicator that has no partial effect is the Empathy indicator. Based on the F test, it is concluded that Tangible, Reliability, Responsiveness, Assurance and Empathy simultaneously have a positive and significant effect on the Quality of BBN-KB Services at the Rantauprapat SAMSAT Office in terms of Sig < 0.05 and based on the calculated F value of 77,894 > from F table 2.31, Tangible, Reliability, Responsiveness, Assurance and Empathy simultaneously have a positive and significant effect on the Quality of BBN-KB Performance at the Rantauprapat SAMSAT Office. Based on the Adjusted R-Square of 0.795, the contribution value of the simultaneous influence of Reliability, Tangible, Responsiveness, Empathy, and Assurance on the Quality of BBN-KB Services is 79.5% and the remaining 20.5% is influenced by other factors outside of this research.